1983
DOI: 10.1111/j.1475-682x.1983.tb01166.x
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Theory of Worker Participation

Abstract: This paper proposes that the emergence of shop-floor worker participation projects in many of the largest corporations in the United States has major theoretical interest because it points to a shift in the structure of American management from Taylorist forms of organization toward "post-Taylorist " systems based on "relative worker autonomy" and limited democratic organization on the shop floor. The postulated shift toward "relative worker autonomy" is explored, first, in terms of the contradictions and fail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

1986
1986
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 10 publications
(4 reference statements)
0
12
0
Order By: Relevance
“…Derber and Schwartz (1983) warned that participation will lead to inherent conflicts over domains of autonomy. They cautioned that workers may become frustrated when they begin to engage in empowering activities and recognize the limitations to such behavior.…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…Derber and Schwartz (1983) warned that participation will lead to inherent conflicts over domains of autonomy. They cautioned that workers may become frustrated when they begin to engage in empowering activities and recognize the limitations to such behavior.…”
mentioning
confidence: 97%
“…Modern organizations have attempted to involve employees in workplace decisions (Derber & Schwartz, 1983;Pacanowksy, 1988;Westin, 1986). Organizational members have become more involved with their respective organizations as a result of organizational democracy (Cheney, 1995;Derber & Schwartz, 1983;Harrison, 1994;Vredenburgh & Brender, 1993;Westin, 1986), employee empowerment (Chiles & Zorn, 1995;EMPLOYEE DISSENT 313 Marshall & Stohl, 1993;Pacanowsky, 1988), and employee participation practices (Dachler & Wilpert, 1978;Derber & Schwartz, 1983;Strauss, 1982).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Miller and Monge (1986) and Derber and Schwartz (1983) have found that participatory involvement is positively correlated with job satisfaction and, to a lesser yet significant degree, with productivity. Participatory communicative behaviors are manifestations of commitment which in turn reinforce commitment attitudes.…”
Section: A Communication Model Of Positive Commitmentmentioning
confidence: 95%
“…Workers usually prefer to participate directly only in decisions affecting their immediate work (Heckscher 1988), and to leave more general concerns to representative bodies like unions or work councils (Westenholz 1979;Miller and Fry 1977). Derber and Schwartz (1983) argued that participatory schemes may generate new conflicts between workers and management while also generating new bases of solidarity among workers.…”
Section: Job Characteristicsmentioning
confidence: 99%